HIV-infected cells are frequently clonally expanded after prolonged antiretroviral therapy: implications for HIV persistence - Frank Maldarelli (Elsevier, 2015)
HIV infection is controlled but not eradicated by combination antiretroviral therapy (cART), and persistence during therapy represents a substantial barrier to strategies to eradicate infection. The nature of persistence is uncertain, and a number of mechanisms have been proposed to explain HIV persistence in vivo, including low-level HIV replication, sanctuary sites for HIV-infected cells, and latent HIV residing within long-lived cells. Analysis of residual viraemia and of cell-associated HIV revealed evidence of multiple copies of identical HIV sequences suggesting infected cells can undergo cellular expansion. Recently, analysis of integration sites in HIV-infected cells derived from peripheral blood lymphocytes of patients undergoing long-term cART revealed direct evidence that HIV-infected cells undergo clonal expansion. These studies demonstrated that clonally expanded populations are common in HIV-infected individuals, persist for prolonged periods and increase in frequency during prolonged therapy. Several analyses reported that site of integration may affect persistence, clonal expansion, or both. As such, expanded populations may represent an important source of infectious HIV during cART. Many HIV integrants are defective for replication, however, and additional research is essential to determine to what degree clonally expanded populations represent a reservoir of replication-competent HIV.